Numerical simulation and tracing to the motion of inclusion particles in casting process. (May 2015) - Zhou, J. X.; Wang, M.; Yin, Y. J.
<x content-type="archive" xml:space="preserve">Abstract</x> This paper mainly performs the tracing of inclusion particles in casting. A Lagrangian model is developed for the motion of inclusions in the flow field. Influences of fluid concentration on the motion of inclusions have been taken into consideration. Two main factors of Basset force influence on the particles' motion trails are studied in particular. The two trails of a particle with and without Basset force acting on it are compared in the heterogeneous flow field. In the end, the motion tracks of 'massless particles' and ponderable particles in a gear casting are obtained. Based on these trails, air trapping and vortex during the pouring process can be found, moreover, these trails can also provide guidance for locating the inclusions in the casting.